PENGARUH GAYA HIDUP DAN KUALITAS PELAYANAN MELALUI KEPUASAN KONSUMEN TERHADAP MINAT BELI ULANG - Silvanda Hilda Zannuba; Dian Prawitasari (Universitas Ahmad Dahlan, 2022)
The purpose of this study is to analyze the mediating role of customer satisfaction in the relationship between a customer's lifestyle and service quality to repurchase intention. The population in this study were the customers of Hijablogue Boutique in Brebes Regency with a number of samples of 100 customers. The sampling technique used in this study is purposive sampling. The collected data were analyzed with Multiple Linear Regression Analysis. The results of the study indicate that lifestyle and service quality has a positive influence on customer satisfaction. Lifestyle, service quality and customer satisfaction have a positive influence on repurchase intention. Lastly, customer satisfaction could mediate the influence of lifestyle and service quality on repurchase intention.